Physicians' Lack of Adherence to National Heart, Lung, and Blood Institute Guidelines for Pediatric Lipid Screening. (October 2015) - Valle, Christopher W.; Binns, Helen J.; Quadri-Sheriff, Maheen; Benuck, Irwin; Patel, Angira
Objectives: To determine adherence to the 2011 National Heart, Lung, and Blood Institute lipid screening guidelines and identify patient factors promoting screening. Methods: Records of children who received well-child care at age 11 years and turned 12 in 2013 were reviewed. Subjects were stratified by guideline-defined dyslipidemia risk based on documented medical or family history risk factors. We defined adherence as the order of a lipid profile when age 11 years or completed lipid screening at 9 to 10 years. Results: Of 298 subjects, 42% were assigned to the dyslipidemia high-risk subgroup. Records of 27.2% demonstrated adherence. Fifty-six percent of high-risk subjects versus 6% of their non-high-risk counterparts received lipid screening by age 12 ( P < .001). Among screened subjects, history of obesity and parental history of dyslipidemia were significantly associated with lipid testing. Conclusions: Lipid screening rates were low. Strategies to increase lipid screening in the primary care setting are needed.